The Main Aspects of Wireless Sensor Nodes for Digital Agriculture - Hanna Antonova (Кібернетика та комп'ютерні технології, 2024)
Introduction. Wireless sensor networks are a part of information and communication technologies and the basis of the Internet of Things technologies. Data are collected, transmitted and processed in real time with the wireless sensor networks. The typical WSN consists of the large number wireless sensor nodes and the coordinator. The wireless network is based on wireless communication standards. Today, WSNs are used in the variety of industries such as medicine, military and digital agriculture. The purpose is to provide a comprehensive analysis of a wireless sensor node for use in digital agriculture. Results. The author analysed wireless communication standards for use in digital agriculture. The typical wireless node architecture is analysed. The parameters of the wireless node are identified. The types of Energy Harvesting Systems (EHS) and their functions are reviewed and analysed. Based on the requires of the wireless node for digital agriculture, the list of photovoltaic energy converters is proposed. In addition, the list of power management integrated circuits is suggested for the Energy Harvesting System. A Classification of Power Supplies for Wireless Sensor Nodes and Networks are developed. The types of sensors for use in digital agriculture are analysed. Conclusions. The main wireless communication standards for digital agriculture are Wi-Fi, IEEE 802.15.4, ZigBee, Bluetooth 4.0, GPRS, 4G, LoRaWAN and NB-IoT. The parameters of the wireless node are identified for further modelling. The list of photovoltaic energy converters is given. The types of power management integrated circuits are proposed. The classification enable to simplify the selection of WSN power supplies for network development. Based on the analysis of sensor parameters for digital agriculture, it is concluded that practically there are no wireless sensors on the world market for the express estimation of plants state.